Safe and appropriate intravenous fluids for children. Issue 6 (20th November 2014) - Sutherland, Adam; Playfor, Stephen
Abstract : Intravenous fluids in children are ubiquitous; however, the evidence base to support the current type of fluid administered and the rate at which to administer is being challenged. Standard fluids (0.45% sodium chloride with 5% glucose) and volumes of administration may give children too much parenteral free water, which has been implicated in fatal iatrogenic hyponatraemia. The UK National Patient Safety Agency mandated action by healthcare organisations to mitigate the risks posed by hypotonic fluids by effectively banning 0.18% sodium chloride with 4% glucose in children, but has not considered other hypotonic fluids. As a result of the attention this issue has received, there is an improved understanding of the physiological mechanisms of water homeostasis in children, notably the action of antidiuretic hormone and the effect that physical illness and medical therapy has on it, but also the effect of chloride in prolonging physical illness and worsening the metabolic disturbance associated with critical illness. There is also a renewed emphasis on the importance of robust clinical research in this subject. Some are considering a physiological approach to fluid therapy. The use of balanced crystalloids like compound sodium lactate or Plasmalyte-148 in children is hampered by the lack of glucose-containing balanced crystalloids suitable for younger children and infants, and an absence of controlled clinical studies in the literature. Balanced crystalloids are being used cautiously in children and are proposed to have economic benefits for healthcare organisations, but definitive research to robustly demonstrate this is needed.